Problem Based Learning Module Based on Curriculum of Freedom for Seven Grade Students of Junior High School - ELDA SELJA PUTRI (English Education Department, 2026)
Abstract: Problem-based learning is an educational method that encourages learners to explore real-world problems and develop solutions as a means of developing knowledge and skills. PBL is a kind of learning where the problem will be the first that is provided and the students whether they are in group or by themselves need to work on that problem such identifying it, solving it, and concluding it. First, based on the observation on the book that is used during the English class, the book that is used is outdated. Second, the students’ problem solving skill is low. Third, it was found that they are in need of a learning aid such as module. The purpose of the research is to develop a learning module for English subject based on the Problem Based. This type of research is Research and Development (R&D). In this research, the researcher chose to follow and addapt the procedure of R&D version of the ADDIE (Analysis-Design-Development-Implementation-Evaluation). The population of the research is all 7th grade students in SMPN 3 Kapur IX. The practicality test results average value of 94.67%, it indicates that the PBL-based module has a very practical value category. The result of normality test there are Kolmogorov-Smirnov values ​​for the Pre-Test and Post-Test categories respectively showing values ​​of 0.145 and 0.177, with significant alpha values ​​of 0.200 and 0.050. All the Kolmogorov-Smirnov alpha significance values ​​exceed the alpha value of 0.05. This indicates that the data have a normal distribution.The homogeneity test results Levene score of 3,456 is obtained with a significant value of 0,069. This score exceeds the alpha value of 0.05. If the homogeneity score exceeds the alpha value of 0.05, it can be concluded that the data is homogeneous.